Diverse serotonin actions of vilazodone reduce l‐3, 4‐dihidroxyphenylalanine–induced dyskinesia in hemi‐parkinsonian rats. Issue 11 (28th November 2018) - Meadows, Samantha M.; Conti, Melissa M.; Gross, Libby; Chambers, Nicole E.; Avnor, Yarden; Ostock, Corinne Y.; Lanza, Kathryn; Bishop, Christopher
ABSTRACT: Background: The serotonergic system is a well‐established modulator of l ‐dopa‐induced dyskinesia. To date, targeting serotonin transporters or serotonin receptor subtype 1A (5‐HT1A ) reduces l ‐dopa‐induced dyskinesia in animal models; however, these strategies have failed to translate clinically. Ideally, a compound acting at both known antidyskinetic sites could optimize serotonin‐mediated approaches. Vilazodone is a selective serotonin reuptake inhibitor and a partial 5‐HT1A agonist approved by the U.S. Food and Drug Administration, situating Vilazodone in a unique position to reduce l ‐dopa‐induced dyskinesia without compromising l ‐dopa‐mediated motor improvements. Objectives : The goal of the present study was to characterize Vilazodone's effects on l ‐dopa‐induced behaviors, neurochemistry and gene expression in unilateral 6‐hydroxydopamine‐lesioned hemi‐parkinsonian rats. Methods : In experiments 1 and 2, l ‐dopa‐naïve and l ‐dopa‐primed animals were coadministered Vilazodone and l ‐dopa daily for 3 weeks to model subchronic use, and behavioral, neurochemical, and messenger RNA (mRNA) expression changes were measured. In experiment 3, dyskinetic behavior was assessed following 5‐HT1A or serotonin receptor subtype 1B blockade prior to Vilazodone–l ‐dopa coadministration. Results : Vilazodone significantly suppressed developing and established l ‐dopa‐induced dyskinesia without compromising the promotor effects of l ‐dopa therapy. In the dopamine‐depleted striatum, Vilazodone–l ‐dopa cotreatment increased dopamine content, suggesting a normalization of dopamine kinetics in dyskinetic brain, and reduced l ‐dopa‐induced c‐Fos and preprodynorphin mRNA overexpression, indicative of attenuated dopamine D1 receptor‐mediated direct pathway overactivity. Only 5‐HT1A antagonism partially attenuated Vilazodone's antidyskinetic efficacy, suggesting both serotonin transporter‐dependent effects and 5‐HT1A receptors in Vilazodone's actions. Conclusions : Our findings show Vilazodone has a serotonin‐dependent effect on rodent l ‐dopa‐induced dyskinesia and implicate the potential for repositioning Vilazodone against l ‐dopa‐induced dyskinesia development and expression in Parkinson's disease patients. © 2018 International Parkinson and Movement Disorder Society